Questão agrária, superexploração e migração temporária : o Vale do Jequitinhonha na dialética do capitalismo dependente - Souza, Cristiane Luíza Sabino de (2016)
We carried out the effort to seek the elements that explain the dialectic of capitalist development from the reality of Latin America, in order to understand the characteristics that appear in this region that despite the intense production of wealth, has the misery of their workers as a constant reality. We tried to explain, because the fundamentals of the contradiction between capital and labor, and the elements that particularize its concrete manifestations, to understand the unique aspects of the same in a specific region, the Jequitinhonha Valley - Minas Gerais. Our specific object of study was the relationship between the temporary migration of workers from the Vale do Jequitinhonha (MG) and the overexploitation of their labor force in the sugar and ethanol industry today. To get the core elements to your understanding we start from a critical perspective, seized in the Marxist tradition. So we built a theoretical and methodological way, to explain the dynamics of uneven and combined development of the capital and its peculiarities in Latin America, evident from the structural dependence, sought to explain the contradictions of this dynamic and build the necessary mediations to understand the peculiarities of working conditions and reproduction of temporary migrants in the Jequitinhonha Valley. We rely on a theoretical seized from the Marxist theory of dependence (TMD) and built a debate structure that gave centrality to dependence categories, development, underdevelopment and inequality, from which we enter the discussion of social issues, land issues and temporary migration. In the search for explanation of the historical and structural processes inherent in the particularity of the Brazilian dependent capitalism, which define the uniqueness of the agrarian question in the Jequitinhonha Valley, expanded understanding of the agrarian question and its relation to overexploitation of the workforce in dependent capitalism, which allowed us to point out the centrality of the same for understanding the contradictions between capital x work in Latin America,